ANALYSIS OF POPULATION VARIATION IN THE PANTANAL BIOME BETWEEN 2010 AND 2022 AND THE IMPROVEMENT OF THE IBGE TERRITORIAL BASE FOR THE 2022 CENSUS - Dias, Nelson Wellausen; Rosa, Lucas Halberstadt da; Saraiva, Fabiano; Cagna, Carlos Eduardo; Lonel, Ivan Donisete; Santos, Fabio Luiz de Oliveira; Silva, Diogo José Nunes da; Tavares, Roberto Ferreira (Ra'e Ga: o Espaço Geográfico em Análise, 2025)
Recent scientific evidence has elucidated the substantial degradation that the Pantanal biome has experienced in recent years. This study aims to provide an analytical examination of the population dynamics within the Pantanal biome by comparing data from the 2010 and 2022 Demographic Censuses, while also incorporating advancements in the geospatial representation of census tracts in the latter census. The methodology employed includes the development and application of SIGBT to improve the tract grid, the analysis of variations in the resident population of rural tracts using heat maps, and a direct comparative analysis of the total number of residents, as well as gender-specific populations, in both censuses. The findings indicate significant disparities in population increases and decreases, as well as variations between male and female residents at the census tract level. Notably, a pronounced decline in the rural population of the Pantanal was documented, particularly within the central-northern region, encompassing the municipalities of Corumbá, Barão de Melgaço, and Aquidauana. The observed negative population flow in rural census tracts between 2010 and 2022, coupled with the occurrence of prolonged droughts and unprecedented wildfires in 2019 and 2020, suggests a potentially detrimental effect of these extreme climatic events on the residential stability of the rural communities in the Pantanal biome.